MAMA PAPUA’S ROLE IN THE SOCIO-ECONOMIC SOCIETY: CASE STUDY OF THE DANI TRIBE IN JAYAWIJAYA REGENCY, PAPUA, INDONESIA - Ningsih, Lukita; Hasudungan, Anju Nofarof; Nababan, Surya Aymanda (Revista Direito e Sexualidade, 2022)
This study aims to mainstream the figure of the Papuan mama (mother) and its role in socio-economic conditions, especially in the Dani tribe in Jayawijaya Regency, Papua, which has so far received little attention. In addition, this research is to enrich the treasures of women in socio-economic history. The existence of the Papuan mama can survive the deplorable economic conditions and the shackled traditional social structure. The ethnographic method used in this research is Naturalistic. The purpose of the naturalistic ethno is to illustrate that the ethnographic research carried out aims to capture the natural character of the Papuan mama and is obtained through direct contact, not through intervention or conditioning. Data collection techniques used by observation, literature review, and documentation. The results show that Papuan mama is the central figure in the household, loved by her children, a symbol of struggle, and a source of inspiration for today’s women, especially in Papua.